Strategi Dakwah Dai Tunggal pada Komunitas Lokal di Desa Ngerejo Tulungagung - Clara Sinta Pratiwi; Afif Mahmudi; Abdul Mu’iz Nidhom (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This study aims to explore the da’wah strategies employed by Ustadz Yani as a solo preacher in instilling Islamic values in Ngrejo Village. Additionally, it seeks to identify the supporting and inhibiting factors affecting his efforts to propagate Islamic teachings in the community. Ngrejo Village is situated approximately 30 kilometers from the city center of Tulungagung, located in Tanggunggunung District at an altitude of 500 meters above sea level. Due to its geographical and social context, Ngrejo is classified as one of the underdeveloped villages in terms of comprehensive knowledge of Islamic values. Ustadz Yani operates independently as a da'i (preacher) to disseminate Islamic teachings in the area. This research employs a qualitative methodology using a case study approach. The study was conducted in Ngrejo Village, Tanggunggunung District, Tulungagung Regency. The key informants for the research include Ustadz Yani as the local preacher, the residents of Ngrejo Village, and the congregation of Nurul Huda Mosque. Data collection techniques utilized in this research include interviews, observation, and documentation, with purposive sampling employed to select participants. The findings reveal that Ustadz Yani's da’wah strategies in instilling Islamic values in Ngrejo Village focus on fostering harmonious social relationships among community members, enhancing public understanding of Islamic principles, serving as a pillar of religious activities in the village, providing religious education, supporting spiritual life, and exemplifying a role model for the local community. Supporting factors include Ustadz Yani's extensive knowledge of Islamic teachings, the support from the congregation of Nurul Huda Mosque, and the availability of mosque facilities. However, challenges include the limited religious knowledge among villagers, the persistence of negative cultural practices, and the physical exhaustion of residents who primarily work as farmers.